Lithium-rich manganese-based layered positive electrode material, preparation method and application
By introducing the lithium-oxygen-vacancies configuration into the lithium-rich manganese-based layered positive electrode material and driving the vacancy defects to the transition metal layer, the problem of insufficient redox activity of the existing LROs positive electrode materials is solved, and its actual reversible capacity and energy density are significantly improved.
Patent Information
- Application Number
- CN202411544585.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-03-14
AI Technical Summary
The actual capacity of the existing lithium-rich layered oxide (LROs) cathode materials is much lower than the theoretical value, and the redox activity is insufficient, making it difficult to effectively improve their actual reversible capacity and energy density.
By introducing a lithium-oxygen-vac configuration (Li-O-□) and driving the vacancy defects into the transition metal layer, more oxygen is stimulated to participate in the redox reaction, thereby activating the redox activity and improving the actual reversible capacity and energy density of the lithium-rich manganese-based layered positive electrode material.
By introducing the lithium-oxygen-vacuum configuration, the oxygen oxidation activity of the lithium-rich manganese-based layered positive electrode material is significantly improved, the charge and discharge capacity is increased, the energy density is improved, and the stability of the material is maintained.
Smart Images

Figure CN119627091A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of positive electrode materials, and in particular to a lithium-manganese-rich layered positive electrode material and a preparation method and application thereof. Background Art
[0002] As the application scope of lithium-ion batteries (LIBs) expands, it is urgent to improve energy density, capacity and operating voltage. Different from the traditional lithium transition metal oxide (LiTMO2, TM is Co, Ni, Mn, etc.) cathode that mainly relies on the redox chemistry of transition metals, lithium-rich layered oxides (LROs), such as xLi2MnO3·(1-x)LiTMO2, mainly rely on anion redox chemistry and can provide more than 250mAh g -1 The maximum capacity and 900Wh kg -1 The above energy density represents a paradigm shift in high energy density lithium batteries.
[0003] The oxygen anion redox activity in LROs originates from the unpaired electrons of lattice oxygen in the special Li-O-Li configuration in the Li2MnO3 component. However, due to insufficient redox activity, the actual capacity of LROs is much lower than the theoretical value. For example, the actual capacity of Li2MnO3 is 155 mAh g -1 , accounting for only 33.7% of the theoretical capacity. Therefore, how to activate the redox activity and how to improve the actual reversible capacity of LROs are still the research focus and difficulty in the field of lithium-ion battery positive electrode material technology. Summary of the invention
[0004] The purpose of the present application is to provide a new lithium-rich manganese-based laminated positive electrode material and its preparation method and application.
[0005] In order to achieve the above objectives, this application adopts the following technical solutions:
[0006] In one aspect, the present application discloses a lithium-rich manganese-based positive electrode material, wherein the lithium-rich manganese-based positive electrode material contains a lithium-oxygen-vacancy configuration (Li-O-□), and the vacancy is located in the transition metal layer. Wherein, "□" represents a vacancy defect; in one implementation of the present application, the molecular formula of the lithium-rich manganese-based positive electrode material is Li(Li x □ y Ni z Co m Mn 1-x-y-z-m )O2. In the molecular formula, x and y are greater than 0, z and m are greater than or equal to 0, and x+y+z+m<1.
[0007] It should be noted that the present application is the first to introduce a lithium-oxygen-vacancy configuration into a lithium-rich manganese-based layered positive electrode material, and drive the vacancy defects into the transition metal layer; therefore, the lithium-oxygen-lithium configuration is included in the lithium-rich manganese-based layered positive electrode material of the present application, and a lithium-oxygen-vacancy configuration that is more susceptible to oxygen redox is also included. The present application creatively utilizes the lithium-oxygen-vacancy configuration to excite more oxygen to participate in the redox reaction, thereby activating the redox activity and improving the actual reversible capacity and energy density of the lithium-rich manganese-based layered positive electrode material.
[0008] In one implementation of the present application, the transition metal layer contains a transition metal, lithium and vacancies. The lithium in the transition metal layer and the lithium in the lithium layer constitute a lithium-oxygen-lithium configuration (Li-O-Li), and the vacancies in the transition metal layer and the lithium in the lithium layer constitute a lithium-oxygen-vacancy configuration.
[0009] In one implementation of the present application, the lithium-oxygen-vacancy configuration accounts for 5%-25% of the total amount of the lithium-oxygen-lithium configuration and the lithium-oxygen-vacancy configuration.
[0010] It should be noted that the key to this application is to creatively introduce the lithium-oxygen-vacancy configuration into the lithium-rich manganese-based laminated positive electrode material to activate the redox activity and improve the capacity and energy density. It can be understood that as long as the lithium-oxygen-vacancy configuration is introduced, the redox activity can be activated to varying degrees and the capacity and energy density can be improved. However, this application study found that when the proportion of lithium-oxygen-vacancy configuration is less than 5%, it cannot bring about obvious effects of capacity improvement and stability improvement; and when the proportion of lithium-oxygen-vacancy configuration is higher than 25%, the framework structure is unstable, which will cause the material stability to deteriorate; therefore, the preferred lithium-oxygen-vacancy configuration is 5%-25%.
[0011] In one implementation of the present application, the transition metal in the transition metal layer is manganese and nickel, or the transition metal is manganese and nickel, and cobalt and / or aluminum. Preferably, the transition metal in the transition metal layer is manganese, nickel and cobalt.
[0012] It should be noted that for the lithium-rich manganese-based positive electrode material of the present application, the elements Mn and Ni are necessary elements, Co can be optional according to needs, and as for Al, its small amount of doping has little effect on the intrinsic properties of the material, so it can also be doped in small amounts.
[0013] In one implementation of the present application, the lithium-rich manganese-based layered positive electrode material is a secondary micron particle composed of primary nanoparticles.
[0014] In one implementation of the present application, the size of the primary nanoparticles is 50-500 nanometers, and the size of the secondary micron particles is 3-20 micrometers.
[0015] Another aspect of the present application discloses a positive electrode sheet, which contains the lithium-rich manganese-based layered positive electrode material of the present application.
[0016] Another aspect of the present application discloses the application of the lithium-rich manganese-based laminated positive electrode material of the present application or the positive electrode plate of the present application in a power lithium battery or a 3C consumer electronics lithium-ion battery.
[0017] Another aspect of the present application discloses a lithium-ion battery, which adopts the positive electrode plate of the present application.
[0018] Another aspect of the present application discloses a method for preparing the lithium-rich manganese-based layered positive electrode material of the present application, which includes subjecting the lithium-rich manganese-based layered positive electrode material to microwave treatment and heat treatment to obtain a lithium-rich manganese-based layered positive electrode material containing a lithium-oxygen-vacancy configuration, and wherein the vacancies are located in the transition metal layer; the microwave treatment conditions are a power of 300-800 W and a microwave time of 1-3 minutes; the heat treatment conditions are sintering at 200-500° C. for 1-4 hours, and the sintering atmosphere is an inert atmosphere.
[0019] It should be noted that the lithium-rich manganese-based layered positive electrode material of the present application is a lithium-rich manganese-based layered positive electrode material prepared by a conventional method, or a conventional lithium-rich manganese-based layered positive electrode material directly purchased; the present application has found that further microwave treatment of the existing conventional lithium-rich manganese-based layered positive electrode material can construct cation vacancy defects, and then heat treatment can drive the vacancy defects to migrate to the transition metal layer, thereby forming the lithium-oxygen-vacancy configuration of the present application, and the vacancies are located in the transition metal layer, that is, the lithium-rich manganese-based layered positive electrode material of the present application is obtained.
[0020] In one implementation of the present application, taking the preparation of lithium-rich manganese-based matrix material by co-precipitation combined with high-temperature sintering as an example, the entire preparation process and microwave treatment and heat treatment include the following steps:
[0021] (1) synthesizing a hydroxide precursor by a coprecipitation method, wherein a transition metal salt mixed aqueous solution, a Na2CO3 aqueous solution, and an NH4OH aqueous solution are stirred for reaction under a nitrogen atmosphere, and then dried to obtain a transition metal carbonate precursor;
[0022] (2) preparing a lithium-rich manganese-based layered material in a high-temperature solid phase, mixing a transition metal carbonate precursor and lithium carbonate to obtain a precursor mixture, and sintering the mixture at 850° C. to 950° C. for 8 to 12 hours in an air or oxygen atmosphere to obtain a lithium-rich manganese-based layered material;
[0023] (3) microwave treatment, mixing the prepared lithium-rich manganese-based layered material with a solvent, stirring evenly, placing in a microwave reactor, adjusting the power to 300 W to 800 W, and the microwave time to 1-3 minutes;
[0024] (4) Heat treatment: sintering the microwave-treated product at 200-500° C. for 1-4 h under an inert atmosphere to obtain the lithium-manganese-rich layered positive electrode material of the present application having a lithium-oxygen-vacancy configuration, wherein the vacancies are located in the transition metal layer.
[0025] In one implementation of the present application, the preparation method of the present application further includes dispersing the lithium-rich manganese-based layered material in a solvent, and then performing microwave treatment and heat treatment.
[0026] In one implementation of the present application, the solvent for dispersing the lithium-rich manganese-based layered material is ethylene glycol.
[0027] In one implementation of the present application, the inert atmosphere used for the heat treatment is argon.
[0028] Due to the adoption of the above technical solution, the beneficial effects of this application are:
[0029] The preparation method of the lithium-rich manganese-based layered positive electrode material of the present application is simple, convenient and fast, has low requirements for production equipment, and is easy to achieve commercial production; more importantly, the introduction of a lithium-oxygen-vacancy configuration into the lithium-rich manganese-based layered positive electrode material can stimulate more oxygen to participate in redox, thereby improving the capacity and energy density of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a scanning electron microscope image of the lithium-rich manganese-based layered positive electrode material prepared in Example 1 of the present application;
[0031] Figure 2 This is a transmission electron microscope result of the lithium-rich manganese-based layered positive electrode material prepared in Example 1 of the present application;
[0032] Figure 3 It is the neutron diffraction pattern and refined structure of the lithium-rich manganese-based layered positive electrode material prepared in Example 1 of the present application;
[0033] Figure 4 This is the first-cycle electrochemical curve of the lithium-rich manganese-based layered positive electrode material prepared in Example 1 of the present application. DETAILED DESCRIPTION
[0034] In the research process of lithium-manganese-rich layered positive electrode materials, this application proposes that the reason why the actual capacity does not reach the theoretical capacity, or even only less than half of the theoretical capacity, is because the existing technology does not have a deep understanding of the activation and stabilization mechanism of redox. Therefore, it is crucial to deeply understand the activation and stabilization mechanism of redox and develop corresponding new synthesis strategies to further improve the actual reversible capacity of LROs.
[0035] In addition, redox reactions have also been widely used in sodium-ion batteries. Different from the Li-O-Li configuration in lithium-ion batteries, a variety of local O configurations with redox activity have appeared in sodium-ion batteries, such as Na-O-Na, Na-O-Li, Na-O-Mg, etc. Recently, the Li-O-□ configuration was first reported in the unique lithium-ion cathode Li2Mn3O7 by lithium / sodium ion exchange method, showing excellent redox activity and good reversibility. However, due to the limitations of the ion exchange method, the crystal structure is constrained by the precursor, and there is currently no method to construct a synthetic strategy for the Li-O-□ configuration in lithium-manganese-rich layered cathode materials.
[0036] In the process of studying lithium-rich manganese-based layered positive electrode materials, the present application found that further microwave treatment of the synthesized lithium-rich manganese-based layered materials can construct cation vacancy defects, and the concentration of cation vacancy defects can be controlled by adjusting the power from 300W to 800W and the microwave time from 1 to 3 minutes. Specifically, at the same power, the longer the microwave time, the higher the concentration of cation vacancy defects; at the same microwave time, higher power can obtain a higher concentration of cation vacancy defects.
[0037] Furthermore, sintering the microwave-treated product at 200-500°C for 1-4h can drive the vacancy defects to migrate to the transition metal layer, thereby forming a Li-O-□ configuration, thereby achieving the purpose of building the Li-O-□ configuration into traditional LROs (especially the Li2MnO3 component), and activating the redox activity and improving the actual reversible capacity and energy density of the lithium-rich manganese-based layered positive electrode material.
[0038] To prepare the lithium-rich manganese-based layered positive electrode material of the present application, which contains a lithium-oxygen-vacancy configuration and in which the vacancies are located in the transition metal layer, the lithium-rich manganese-based layered material can be first prepared using an existing preparation method, or a conventional lithium-rich manganese-based layered material can be purchased and then subjected to microwave treatment and heat treatment. In one implementation of the present application, the preparation of the lithium-rich manganese-based layered material by coprecipitation combined with high-temperature sintering is used as an example for explanation.
[0039] The lithium-rich manganese-based positive electrode material is prepared by co-precipitation method combined with high temperature sintering, and then subjected to microwave treatment and heat treatment, specifically including the following steps:
[0040] (1) Synthesis of hydroxide precursor by coprecipitation: a 0.3-3.0 mol L -1 The mixed aqueous solution of metal salts was pumped into a homemade continuous stirred tank reactor under nitrogen atmosphere. -1 Na2CO3 aqueous solution and 0.2-2.0 mol L -1NH4OH aqueous solution was pumped into the reactor as a precipitant and a complexing agent respectively. Stirring was carried out at a constant speed and the stirring speed was maintained at 500-1000 rpm / s. The reaction was carried out for 6-15 hours and dried in a vacuum oven at 80°C overnight.
[0041] (2) Obtaining a layered product in a high-temperature solid phase: Mix a transition metal carbonate precursor and lithium carbonate, wherein the lithium content is 100% to 107% of the total transition metal content, to obtain a precursor mixture. Place the mixture in a high-temperature reactor and sinter it at 850°C to 950°C for 8 to 12 hours in an air atmosphere to obtain a layered lithium-rich manganese-based positive electrode material.
[0042] (3) Microwave treatment to construct cation vacancy defects: Mix the lithium-rich manganese-based cathode material with ethylene glycol at a mass ratio of 1:2 to 1:20 and stir at a constant speed for 10 to 20 minutes. After the mixture is evenly mixed, place it in a microwave reactor, adjust the power to 300W to 800W, and microwave for 1 minute to 3 minutes to control the concentration of cation defects.
[0043] (4) Heat treatment drives vacancy defects to migrate to the transition metal layer: The heat treatment process after microwave treatment, including sintering temperature and sintering time, is used to achieve the migration of cationic vacancy defects to the transition metal layer to form a Li-O-□ structure. The sintering temperature can be adjusted from 200-500°C, the sintering time can be adjusted from 1h-4h, and the sintering atmosphere is an inert atmosphere, such as argon.
[0044] The present invention is further described in detail below by means of specific implementation modes in combination with the accompanying drawings. The following examples are only used to further illustrate the present application and should not be construed as limiting the present application.
[0045] Example 1
[0046] (1) Synthesis of hydroxide precursor Mn by coprecipitation method 0.662 Ni 0.163 Co 0.175 CO3: The concentration is 0.4 mol L -1 A mixed aqueous solution of NiSO4·6H2O, CoSO4·7H2O and MnSO4·5H2O was pumped into a continuous stirred tank reactor (1 L) under nitrogen atmosphere. -1 Na2CO3 aqueous solution and 0.315 mol L -1 NH4OH aqueous solution was pumped into the reactor as a precipitant and a complexing agent. The stirring speed was maintained at 1000 rpm / s. The mixture was reacted for 12 hours, filtered, washed with deionized water for 3 times, and dried in a vacuum oven at 80°C overnight.
[0047] (2) High-temperature solid-phase sintering is used to obtain the product: Li2CO3 and the above precursor are mixed and ground evenly according to a molar ratio of Li:TM=1.01:1, where TM is the total molar amount of the transition metal element, and calcined at 950°C for 8 hours, and cooled naturally to obtain the product Li 1.153 Ni 0.138 Co 0.148 Mn 0.561 O2 material.
[0048] (3) Preparation of Li-O-vacancy configuration by microwave and heat treatment: The Li prepared in step (2) above 1.153 Ni 0.138 Co 0.148 Mn 0.561 The O2 material and ethylene glycol were mixed evenly at a mass ratio of 1:20. The mixture was then placed in a microwave reactor and reacted for 3 minutes at a power of 500 W, filtered and washed with deionized water, and then dried. The dried sample was heated at 400 ° C for 2 hours under an argon atmosphere and cooled naturally to obtain the lithium-rich manganese-based positive electrode material of this example.
[0049] The lithium-rich manganese-based positive electrode material prepared in this example was observed by scanning electron microscopy. Figure 1 shown. Figure 1 The results show that dense secondary particles with an average particle size of 15 microns were prepared in this example.
[0050] The lithium-rich manganese-based positive electrode material prepared in this example was observed by transmission electron microscopy. Figure 2 shown. Figure 2 The results show that the lithium-rich manganese-based layered positive electrode material prepared in this example can clearly observe the internal Li2MnO3 Li-rich structure area (blue box) and the layered LiTMO2 area (green box).
[0051] The X-ray diffraction analysis of the lithium-rich manganese-based positive electrode material prepared in this example is shown in the following results: Figure 3 According to the structure refinement results of the X-ray diffraction pattern, the content of lithium-oxygen-vacancy configuration in the lithium-manganese-based positive electrode material prepared in this example is 18.8%, and the content of lithium-oxygen-lithium configuration is 81.2%.
[0052] Electrochemical test: Li-containing lithium-oxygen-vacancy configuration 1.153 Ni 0.138 Co 0.148 Mn 0.561 O2, carbon black and PVDF were mixed in a mass ratio of 80:10:10 and ground in a mortar to prepare the positive electrode sheet. The active material loading was about 4 mg cm -2Lithium half-cells were prepared using 2032-type button cells, Celgard 2325 separators and 1.2 mol L -1 The GEN II electrolyte (LiPF6 dissolved in a 3:7 volume ratio EC / EMC mixed solvent) was used to charge the half-cell at 2.0-4.8V (vs Li + / Li) cycle. At the same time, the Li 1.153 Ni 0.138 Co 0.148 Mn 0.561 The O2 material was used as a control, i.e., the product of step (2).
[0053] No Li-O-vacancy Li 1.153 Ni 0.138 Co 0.148 Mn 0.561 O2 and Li containing Li-O-vacancy configuration 1.153 Ni 0.138 Co 0.148 Mn 0.561 The first electrochemical curve of O2 is as follows Figure 4 shown. Figure 4 The results show that the capacity contributed by oxygen oxidation increased by 8-12% thanks to the introduction of Li-O-vacancy configuration.
[0054] This example calculates the change of charge and discharge capacity at 25℃ and 45℃. Specifically, at 25℃, the charge capacity increases from 295.92mAh g-1 to 45.92mAh g-1 without Li-O-vacancy configuration material. -1 The capacity of the material containing Li-O-vacancies was increased to 311.08 mAh g -1 The discharge capacity of the material without Li-O-vacancies is 282.18 mAh g -1 The results show that the Li-O-vacancy-containing material has a 304.65 mAh g -1 At 45 °C, the charge capacity increased from 323.61 mAh g-1 to 323.61 mAh g-2 without Li-O-vacancy configuration. -1 The performance of the Li-O-vacancy material was improved to 340.52 mAh g -1 The discharge capacity of the material without Li-O-vacancies is 311.46 mAh g -1 The performance of the Li-O-vacancy material was improved to 318.03 mAh g -1 .
[0055] Example 2
[0056] (1) Synthesis of hydroxide precursor Ni by coprecipitation method 0.25 Mn 0.75CO3: The concentration is 0.5 mol L -1 A mixed aqueous solution of NiSO4·6H2O and MnSO4·5H2O was pumped into a continuous stirred tank reactor (1 L) under nitrogen atmosphere. -1 Na2CO3 aqueous solution and 0.3 mol L -1 NH4OH aqueous solution was pumped into the reactor as a precipitant and a complexing agent. The stirring speed was maintained at 1000 rpm / s. The mixture was reacted for 10 hours, filtered, washed with deionized water for 3 times, and dried in a vacuum oven at 80°C overnight.
[0057] (2) High-temperature solid-phase sintering is used to obtain the product: Li2CO3 and the above precursor are mixed and ground evenly according to a molar ratio of Li:TM=1.03:1, where TM is the total molar amount of the transition metal element, and calcined at 925°C for 10 hours, and cooled naturally to obtain the product Li 1.2 Ni 0.2 Mn 0.6 O2 material.
[0058] (3) Preparation of Li-O-vacancy configuration by microwave and heat treatment: Li 1.2 Ni 0.2 Mn 0.6 The O2 material and ethylene glycol were mixed evenly at a mass ratio of 1:10. The mixture was then placed in a microwave reactor, reacted for 1 minute at a power of 600 W, filtered and washed with deionized water, and then dried. The dried sample was heated at 400 ° C for 2 hours under an argon atmosphere, and cooled naturally to prepare the lithium-rich manganese-based positive electrode material of this example.
[0059] Scanning electron microscopy, transmission electron microscopy and X-ray diffraction analysis were performed in the same manner as in Example 1. The results showed that dense secondary particles with a particle size of 10 μm were prepared in this example, in which Li-rich structure regions and layered LiTMO2 regions were clearly observed, and the content of lithium-oxygen-vacancy configuration was 10%, and the content of lithium-oxygen-lithium configuration was 90%.
[0060] Electrochemical test: Li-containing lithium-oxygen-vacancy configuration 1.2 Ni 0.2 Mn 0.6 O2 was mixed with carbon black and PVDF in a mass ratio of 80:10:10 and ground in a mortar to prepare the positive electrode sheet. The active material loading was about 5 mg cm -2The lithium half-cell was prepared using a 2032-type button cell, Celgard 2325 separator and 1.2 mol L-1 GEN II electrolyte (LiPF6 dissolved in a 3:7 volume ratio EC / EMC mixed solvent), and the half-cell was charged at 2.0-4.8 V (vs Li + / Li) cycle. At the same time, the Li 1.2 Ni 0.2 Mn 0.6 The O2 material was used as a control, i.e., the product of step (2).
[0061] No Li-O-vacancy Li 1.2 Ni 0.2 Mn 0.6 O2 and Li containing Li-O-vacancy configuration 1.2 Ni 0.2 Mn 0.6 The first electrochemical curve of O2 shows that the capacity contributed by oxygen oxidation increased by 9-10% due to the introduction of Li-O-vacancy configuration. At 25-45℃, the charge and discharge capacity increased significantly.
[0062] Example 3
[0063] (1) Synthesis of hydroxide precursor Ni by coprecipitation method 0.33 Mn 0.67 CO3: The concentration is 0.4 mol L -1 A mixed aqueous solution of NiSO4·6H2O and MnSO4·5H2O was pumped into a homemade continuous stirred tank reactor (1 L) under nitrogen atmosphere. -1 Na2CO3 aqueous solution and 0.28 mol L -1 NH4OH aqueous solution was pumped into the reactor as a precipitant and a complexing agent, respectively. The mixture was stirred at 1000 rpm / s for 12 hours, filtered, washed with deionized water for 3 times, and dried in a vacuum oven at 80°C overnight.
[0064] (2) High-temperature solid-phase sintering is used to obtain the product: Li2CO3 and the above precursor are mixed and ground evenly according to a molar ratio of Li:TM=1.05:1, where TM is the total molar amount of the transition metal element, and calcined at 850°C for 12 hours, and cooled naturally to obtain the product Li 1.2 Ni 0.267 Mn 0.533 O2 material.
[0065] (3) Preparation of Li-O-vacancy configuration by microwave and heat treatment: Li 1.2 Ni 0.267 Mn0.533 The O2 material and ethylene glycol were mixed evenly at a mass ratio of 1:10. The mixture was then placed in a microwave reactor, reacted for 1 minute at a power of 500 W, filtered and washed with deionized water, and then dried. The dried sample was heated at 300 ° C for 4 hours under an argon atmosphere, and cooled naturally to prepare the lithium-rich manganese-based positive electrode material of this example.
[0066] Scanning electron microscopy, transmission electron microscopy and X-ray diffraction analysis were performed in the same manner as in Example 1. The results showed that dense secondary particles with a particle size of 4 μm were prepared in this example, inside which Li-rich structure regions and layered LiTMO2 regions were clearly observed, and the content of lithium-oxygen-vacancy configuration was 14%, and the content of lithium-oxygen-lithium configuration was 86%.
[0067] Electrochemical test: Li-containing lithium-oxygen-vacancy configuration 1.2 Ni 0.267 Mn 0.533 O2 was mixed with carbon black and PVDF in a mass ratio of 80:10:10 and ground in a mortar to prepare the positive electrode sheet. The active material loading was about 5 mg cm -2 Lithium half-cells were prepared using 2032-type button cells, Celgard 2325 separators and 1.2 mol L -1 The GEN II electrolyte (LiPF6 dissolved in a 3:7 volume ratio EC / EMC mixed solvent) was used to charge the half-cell at 2.0-4.8V (vs Li + / Li) cycle. At the same time, the Li 1.2 Ni 0.267 Mn 0.533 The O2 material was used as a control, i.e., the product of step (2).
[0068] No Li-O-vacancy Li 1.2 Ni 0.267 Mn 0.533 O2 and Li containing Li-O-vacancy configuration 1.2 Ni 0.267 Mn 0.533 The first electrochemical curve of O2 shows that the capacity contributed by oxygen oxidation increased by 11-12% due to the introduction of Li-O-vacancy configuration. The charge and discharge capacity also increased significantly under the conditions of 25-45℃.
[0069] Example 4
[0070] (1) Synthesis of hydroxide precursor Mn by coprecipitation method 0.675 Ni 0.1625 Co 0.1625CO3: The concentration is 0.3 molL -1 A mixed aqueous solution of NiSO4·6H2O, CoSO4·7H2O and MnSO4·5H2O was pumped into a homemade continuous stirred tank reactor (1 L) under nitrogen atmosphere. -1 Na2CO3 aqueous solution and 0.21 mol L -1 NH4OH aqueous solution was pumped into the reactor as a precipitant and a complexing agent. The stirring speed was maintained at 1000 rpm / s. The mixture was reacted for 12 hours, filtered, washed with deionized water for 3 times, and dried in a vacuum oven at 80°C overnight.
[0071] (2) High-temperature solid-phase sintering is used to obtain the product: Li2CO3 and the above precursor are mixed and ground evenly according to a molar ratio of Li:TM=1.05:1, where TM is the total molar amount of the transition metal element, and calcined at 950°C for 12 hours, and cooled naturally to obtain the product Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 material.
[0072] (3) Preparation of Li-O-vacancy configuration by microwave and heat treatment: The Li prepared in step (2) above 1.2 Ni 0.13 Co 0.13 Mn 0.54 The O2 material and ethylene glycol were mixed evenly at a mass ratio of 1:10. The mixture was then placed in a microwave reactor and reacted for 1.5 minutes at a power of 600 W, filtered and washed with deionized water, and then dried. The dried sample was heated at 400 ° C for 4 hours under an argon atmosphere and cooled naturally to obtain the lithium-rich manganese-based positive electrode material of this example.
[0073] Scanning electron microscopy, transmission electron microscopy and X-ray diffraction analysis were performed in the same manner as in Example 1. The results showed that dense secondary particles with a particle size of 10 μm were prepared in this example, inside which Li-rich structure regions and layered LiTMO2 regions were clearly observed, and the content of lithium-oxygen-vacancy configuration was 12%, and the content of lithium-oxygen-lithium configuration was 88%.
[0074] Electrochemical test: Li-containing lithium-oxygen-vacancy configuration 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 was mixed with carbon black and PVDF in a mass ratio of 80:10:10 and ground in a mortar to prepare the positive electrode sheet. The active material loading was about 4 mg cm -2Lithium half-cells were prepared using 2032-type button cells, Celgard 2325 separators and 1.2 mol L -1 The GEN II electrolyte (LiPF6 dissolved in a 3:7 volume ratio EC / EMC mixed solvent) was used to charge the half-cell at 2.0-4.8V (vs Li + / Li) cycle. At the same time, the Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 The O2 material was used as a control, i.e., the product of step (2).
[0075] No Li-O-vacancy Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 and Li containing Li-O-vacancy configuration 1.2 Ni 0.13 Co 0.13 Mn 0.54 The first electrochemical curve of O2 shows that the capacity contributed by oxygen oxidation increased by 9-12% due to the introduction of Li-O-vacancy configuration. The charge and discharge capacity also increased significantly under the conditions of 25-45℃.
[0076] The above specific examples are used to illustrate the present invention, which is only used to help understand the present invention and is not intended to limit the present invention. For those skilled in the art, according to the concept of the present invention, some simple deductions, modifications or substitutions can be made.
Claims
1. A lithium-rich manganese-based layered positive electrode material, characterized in that: The lithium-manganese-rich layered positive electrode material contains a lithium-oxygen-vacancy configuration, and the vacancies are located in the transition metal layer.
2. The lithium-rich manganese-based layered positive electrode material according to claim 1, characterized in that: The transition metal layer contains transition metal, lithium and vacancies; The lithium in the transition metal layer and the lithium in the lithium layer form a lithium-oxygen-lithium configuration, and the vacancies in the transition metal layer and the lithium in the lithium layer form a lithium-oxygen-vacancy configuration.
3. The lithium-rich manganese-based layered positive electrode material according to claim 2, characterized in that: The lithium-oxygen-vacancy configuration accounts for 5%-25% of the total amount of the lithium-oxygen-lithium configuration and the lithium-oxygen-vacancy configuration.
4. The lithium-rich manganese-based layered positive electrode material according to any one of claims 1 to 3, characterized in that: The transition metal in the transition metal layer is manganese, and at least one of nickel, cobalt and aluminum; Preferably, the transition metal in the transition metal layer is manganese and nickel, or the transition metal in the transition metal layer is manganese and nickel, and cobalt and / or aluminum.
5. The lithium-rich manganese-based layered positive electrode material according to any one of claims 1 to 3, characterized in that: The lithium-rich manganese-based layered positive electrode material is secondary micron particles composed of primary nanoparticles; Preferably, the size of the primary nanoparticles is 50-500 nanometers, and the size of the secondary microparticles is 3-20 micrometers.
6. A positive electrode sheet, characterized in that: A lithium-rich manganese-based layered positive electrode material comprising any one of claims 1 to 5.
7. Use of the lithium-rich manganese-based layered positive electrode material according to any one of claims 1 to 5, or the positive electrode plate according to claim 6 in power lithium batteries or 3C consumer electronic lithium-ion batteries.
8. A lithium ion battery, characterized in that: The positive electrode sheet according to claim 6 is adopted.
9. The method for preparing the lithium-rich manganese-based layered positive electrode material according to any one of claims 1 to 5, characterized in that: The method comprises subjecting a lithium-rich manganese-based layered material to microwave treatment and heat treatment to obtain a lithium-rich manganese-based layered positive electrode material having a lithium-oxygen-vacancy configuration, wherein the vacancies are located in the transition metal layer; The microwave treatment conditions are as follows: power 300-800W, microwave time 1-3 minutes; The heat treatment conditions are sintering at 200-500° C. for 1-4 hours, and the sintering atmosphere is an inert atmosphere.
10. The preparation method according to claim 9, characterized in that: The method also includes dispersing the lithium-manganese-rich matrix material in a solvent, and then performing microwave treatment and heat treatment; Preferably, the solvent is ethylene glycol; Preferably, the inert atmosphere is argon.